A framework of knowledge sharing in collaborative research activities - Mona Hussain Al-Sayed; Halina Mohamed Dahlan, supervisor; Fakulti Komputeran (2013)
Thesis (Sarjana Sains Teknologi Maklumat - Pengurusan)) - Universiti Teknologi Malaysia, 2013